Blind adolescents' anger levels and expressing their anger styles [Görme engelli ergenlerin öfke düzeyi ve öfke ifâde tarzlarmm incelenmesi] - (:unkn) unknown (My University, 2011)
Objectives: Adolescents in each age group as one of the major emotional expressions of anger. Appropriate ways of expressing anger cannot be revealed if not removed or adolescent physical, psychological and social problems may result. The aims of this study investigate blind adolescents' anger levels, ways of expressing themselves and relationships with variables as gender, age, parents' educational background. Method: The study was being fulfilled 59 blind adolescents that continuous primary school for blind, ages 11 to 17 and only visually handicapped. Data was collected with an information form that includes demographic information and State-Trait Anger Expression Inventory. Findings: The mean age of blind adolescent participated in the survey is 14.29±0.15. Mean of blind adolescents' anger points was found as continuous anger x=25.17±6.37, anger control x=19.88±6.17, anger-out x=18.90±6.09 and anger-in x=18.69±5.61. When mean values were examined according to gender, it was found that males had higher mean values from continuous anger and anger-out scales than females and the difference was found statistically significant. Discussion and Conclusion: Blind adolescent of the study have high level of continuous anger and male adolescents are more likely to outwardly express their anger. According to gender, it was found that males had higher mean values from continuous anger and anger-out scales than females and the difference was found statistically significant. Blind adolescents have not been found in the literature, a similar study, found similar results in terms of gender in the general adolescent group.
Keywords: Anger levels; Blind adolescent; Styles of anger expressions